Profile and characteristics of the adequacy of blood transfusions in Trauma Intensive Care. A cross sectional multicenter study - Juárez-Vela, Raúl; Quintana-Diaz, Manuel; Rodríguez-Calvo, Antonio; Santos-Sánchez, José Ángel; Gero-Escapa, María; Gallego-Curto, Elena; Satústegui-Dordá, Pedro José; Sánchez-González, Juan Luis; Jericó, Carlos; Ruiz de Viñaspre-Hernández, Regina; Gil-Fernández, Guadalupe; García-Erce, José Antonio (Frontiers in Public Health, 2023)
Introduction Major trauma is one of the major health care problems facing modern society, trauma systems require careful planning to achieve an ideal level of coverage for the population. The Patient Blood Management Program is an integrated and global strategy to provide patient care that aims to assess and address, when possible, the etiology of blood abnormalities rather than transfuse without treating the underlying cause. We aimed to describe the factors that are associated with the clinical decision to transfuse polytraumatized patients admitted to the Intensive Care Unit (ICU). Method We performed a cross sectional multicenter study of patients admitted to ICUs for trauma in 14 Spanish hospitals from September 2020 to December 2021. Results A total of 69 patients were treated in the emergency room due to polytrauma, 46% of them were considered serious in the initial triage. Thirty were caused by a fall from considerable height (43.47%), followed by 39 patients admitted due to trac accidents (56.52%). The location of the trauma was mainly cranioencephalic, followed by thoracic trauma. Of the 69 patients, 25 received a blood transfusion during their ICU stay (36.23%). Discussion No significant differences were observed between transfused and non-transfused patients, except for the severity scales, where transfused patients have a higher score on all the scales assessed in the ICU except for the Revised Trauma Score. As we can see, the incidence of kidney failure was also different between the groups analyzed, reaching 44.00% in transfused patients and 13.64% in the group of patients without blood transfusion, p = 0.005. In this sense, 92.00% of the transfusions performed were inadequate according to the criteria of Hb in blood prior to the decision to transfuse (Hb < 9). Our data support the need to consider clinical practice guidelines regarding blood transfusion and its practices.